Genetic diversity in Phaseolus spp. as revealed by SDS-PAGE markers - Sammour, R.H.=700 1 Radwan, S.A.; El-Koly, A.
(En, Fr, Es)
Ilus., 43 ref.
Keywords: PHASEOLUS; VARIACION GENETICA; MARCADORES GENETICOS; PROTEINAS VEGETALES; ITALIA